2 - L’Université Africaine : Facteur de Division Sociale et de Dépendance économique - VERHAEGEN, BENOIT (Africa Development, 1979)
In his article the author argues that up to now African Universities have not fulfilled the roles expected of them during the time of independence in the early sixties. Instead of constituting an agency of national integration by the ela boration of a common cultural and ideological basis, they have widely contributed to the development of national bourgeoisies thus accentuating social inegalities. Instead of providing the theoretical basis for real economic and political independence the African University has become a strong instrument used by imperialism to organize and to justify the dependence and exploitation of African peoples. Taking the example of University of Zambia the author shows that African Universities in general as scientific and cultural institutions failed to support the process of political as well as cultural and economic decolonization. Instead of new alternative concepts they have stuck to an occidental materialist ideology thus perpetuating the traditional role of the University in Europe and North America; that is, granting social profits to those who managed to get univer sity degree. Even if African University degrees don't constitute an immediate « billet d'entrée » to the ruling classes, the post-graduate knows - and has the feeling of moral superiority - that one day or another those who are or shall be in power will require his specific abilities.